Understanding "Internet Plus Healthcare" in China: Policy Text Analysis - Feng Yang; Huilin Shu; Xiaoqian Zhang (JMIR Publications, 2021)
BackgroundThe combination of the internet and healthcare has excellent benefits and far-reaching positive effects in improving service efficiency and promoting social equity. The role of the "internet plus healthcare" (IPHC) has been recognized, especially during the COVID-19 pandemic. This new healthcare model is also familiar to people and shows a bright prospect. ObjectiveThis article seeks to accurately understand and fully grasp the characteristics of IPHC policies that can enlighten the formulation of future policies. MethodsThe content analysis method was used to analyze China's IPHC policies collected from the Beida Fabao database and several official websites. ResultsWe found that the development of IPHC policy has gone through 4 stages and is currently entering a phase of rapid development. IPHC policymakers are primarily health administrative departments. In addition, policy instruments are classified into either supply, environment, or demand, and policy themes can be summarized into 4 categories: facilities, technology, service, and management. ConclusionsChina's IPHC policy has good prospects from the perspective of development trends. The health administrative departments mainly lead the development of China's IPHC policy. It is suggested that these departments involve other stakeholders (ie, medical workers, medical industries, and technology sectors) in formulating policies. Policies prefer to use supply-based and environment-based policy instruments. The policy themes emphasize improving infrastructure construction and high-quality diagnostic and treatment services, strengthening the supporting role of information technology, and ensuring all stakeholders understand their responsibilities.